HARUSKAH IKLAN DILENYAPKAN - Tinarbuko, Sumbo (Nirmana, 2002)
Must advertisement be vanished? Observing the percentage between the pros and the cons carried out at random concerning the existence of advertisement%2C we will find out an emotional response%2C i.e. it must be vanished from this earth. The sins performed by the advertisement seem unforgivable. But if we analyze the mass (chaos) the advertisement problems more deeply%2C we should negotiate and introspect as well among all sides. Abstract in Bahasa Indonesia : Haruskah iklan dilenyapkan? Jika melihat presentase secara acak antara yang pro dan kontra terhadap keberadaan iklan%2C maka jawaban emosionalnya%2C iklan harus dilenyapkan dari muka bumi ini! Sebab dosa iklan sudah tidak bisa dimaafkan lagi. Tetapi jika kita kaji lebih dalam carut marut perihal periklanan tersebut%2C kita bisa melakukan negosiasi sekaligus introspeksi antarpara pihak. negotiation%2C introspection of all sides.